Genome-wide transcriptional and physiological responses to drought stress in leaves and roots of two willow genotypes. Issue 1 (December 2015) - Pucholt, Pascal; Sjödin, Per; Weih, Martin; Rönnberg-Wästljung, Ann; Berlin, Sofia
Abstract Background Drought is a major environmental stress that can have severe impacts on plant productivity and survival. Understanding molecular mechanisms of drought responses is crucial in order to breed for drought adapted plant cultivars. The aim of the present study was to investigate phenotypic and transcriptional drought responses in two willow genotypes (520 and 592) originating from an experimental cross betweenS .viminalis × (S. viminalis × S. schwerinii ). Willows are woody perennials in the Salicaceae plant family that are grown as bioenergy crops worldwide. Methods An experiment was conducted where plants were exposed to drought and different eco-physiological parameters were assessed. RNA-seq data was furthermore generated with the Illumina technology from root tips and leaves from plants grown in drought and well-watered (WW) conditions. The RNA-seq data was assembled de novo with the Trinity assembler to create a reference gene set to which the reads were mapped in order to obtain differentially expressed genes (DEGs) between the drought and WW conditions. To investigate molecular mechanisms involved in the drought response, GO enrichment analyses were conducted. Candidate genes with a putative function in the drought response were also identified. Results A total of 52, 599 gene models were obtained and after filtering on gene expression (FPKM ≥ 1), 35, 733 gene models remained, of which 24, 421 contained open reading frames. A total of 5, 112 unique DEGs were identified between drought and WW conditions, of which the majority were found in the root tips. Phenotypically, genotype 592 displayed less growth reduction in response to drought compared to genotype 520. At the transcriptional level, genotype 520 displayed a greater response in the leaves as more DEGs were found in genotype 520 compared to genotype 592. In contrast, the transcriptional responses in the root tips were rather similar between the two genotypes. A core set of candidate genes encoding proteins with a putative function in drought response was identified, for example MYBs and bZIPs as well as chlorophyll a/b binding proteins. Discussion We found substantial differences in drought responses between the genotypes, both at the phenotypic and transcriptional levels. In addition to the genotypic variation in several traits, we also found indications for genotypic variation in trait plasticity, which could play a role in drought adaptation. Furthermore, the two genotypes displayed overall similar transcriptional responses in the root tips, but more variation in the leaves. It is thus possible that the observed phenotypic differences could be a result of transcriptional differences mostly at the leaf level. Conclusions This study has contributed to a better general understanding of drought responses in woody plants, specifically in willows, and has implications for breeding research towards more drought adapted plants.